Organizing Valuations: A Pragmatic Inquiry - Amalie Martinus Hauge (Copenhagen Business School (CBS), 2017)
With this dissertation I take up a problem currently traversing popular, political and academic arenas, namely the potential demise of values in public organizations allegedly instigated by management tools deriving from industrial sectors. Taking a pragmatic stance, inspired by John Dewey, this dissertation sets out to develop a practical and situation-based understanding of the relationship between these management tools, values and organizations, which can contribute to pushing forward the currently detached and polarized debates over New Public Management. In this endeavor the dissertation engages with the conceptual operations of creating increased interaction between two relevant theoretical fields namely valuation studies and organization theory, as well as the observational operations of conducting an empirical study in a Danish hospital department.
hdl:10398/9483
Keywords: 650